Torstein Utigard: The Man - The Scientist - COM 2015 - 54th Annual Conference of Metallurgists held in Conjunction with AMCAA - America's Conference on Al Alloys - M. Barati; C. Díaz (Canadian Institute of Mining, Metallurgy and Petroleum, 2015)
Prof. Torstein Utigard's untimely death, in the spring of 2012, put an abrupt end to a meritorious career in the field of high temperature chemical process metallurgy. As an academic in the Department of Materials Science and Engineering of the University of Toronto, Torstein made solid contributions to the advancement of knowledge pertaining to production and refining of both nonferrous and light metals, and to the development of inquisitive and innovative young people in extractive metallurgy. In this profile, the authors highlight aspects of Torstein's rich personality and of his contributions to his field of expertise.